Annual Plan 1976-77 Agriculture and Allied Group of Schemes, Government of Punjab - Planning Commission (Planning Commission, 1976)
Agriculture is the mainstay of the economy of Punjab, since 80% of the population in the State derives its livelihood directly and indirectly from agriculture. Punjab is known as the granary of India and has been contributing annually about 60% to the national wheat pool and 25% to the national rice pool. Still agriculture is not free from problems and difficulties. Some of the problems afflicting the agricultural sector in the State are inadequate and uncertain rainfall, shortage of power for irrigation purposes, high prices of fertilizers and other inputs, sale of spurious seeds, existence of culturable wastes and kallar lands, shortage of capital resources with the farmers, vulnerability of high yielding varieties to pests and diseases, inadequate and unscientific storage facilities, depletion of soil and water resources and last but not the least the existence of economic inequalities in the agricultural sector. Their urgent solution is essential for securing optimum productivity and an ever-rising curve of agricultural output. The State Government has been making continuous and strenuous efforts to solve the above problems through the Five Year Plans. The Punjab Agricultural University, Agriculture, Soil Conservation and Irrigation Departments have been formulating and implementing various plan schemes to solve the problems of agricultural sector since the very inception of Planning in the State. The Departments have been fixing targets both on five yearly and annual bases in consonance with the overall policy and strategy laid down by the Central Government.
Agriculture and Allied Group of Schemes
Government of Punjab